2017
DOI: 10.1159/000477935
|View full text |Cite
|
Sign up to set email alerts
|

The SARC-F Questionnaire: Diagnostic Overlap with Established Sarcopenia Definitions in Older German Men with Sarcopenia

Abstract: Background: The high relevance of sarcopenia for the aging societies of most developed nations is emphasized by its recent inclusion in the ICD-10-CM (M62.84). However, diagnosing sarcopenia is a daunting task. Apart from varying definitions, the proper assessment of recognized sarcopenia criteria is time and cost consuming. A short and inexpensive screening tool may thus be welcome for clinicians and others working in the area of gerontology. Recently, a simple questionnaire was provided (SARC-F) that may ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 15 publications
1
16
0
1
Order By: Relevance
“…SARC‐F is a self‐reported five‐item questionnaire that can be performed rapidly without any invasion 25,26 . A previous study found that SARC‐F demonstrated high specificity for identifying sarcopenia in community‐based elderly people 27–29 . However, the low sensitivity of SARC‐F restricted its clinical usefulness.…”
Section: Discussionmentioning
confidence: 99%
“…SARC‐F is a self‐reported five‐item questionnaire that can be performed rapidly without any invasion 25,26 . A previous study found that SARC‐F demonstrated high specificity for identifying sarcopenia in community‐based elderly people 27–29 . However, the low sensitivity of SARC‐F restricted its clinical usefulness.…”
Section: Discussionmentioning
confidence: 99%
“…In SARC-F (Strength, Assistance with walking, Rise from a chair, Climb stairs, and Falls) questionnaire, each of the five items has 2 points for a total of 10 points, and a total score ≥4 points indicates that the risk of sarcopenia is increased. The latest research on SARC-F shows that compared with diagnostic criteria proposed by authoritative sarcopenia-working groups, such as EWGSOP, IWGS, and FNIH, SARC-F has a higher detection overlap and higher specificity for the muscle function test, which is an excellent test for identifying muscle function damage and muscle atrophy (20,21). Thus, SARC-F is a better screening test for functional measures and it is reasonable to regard SARC-F as the first simple step in the hierarchical screening process.…”
Section: Sarc-f Combined With Calf Circumference (Sarc-calf)mentioning
confidence: 99%
“…In 2013, Malmstrom and Morley developed this questionnaire to screen sarcopenia simply, rapidly and conveniently, and suggested that a total score of ≥4 points was considered to indicate sarcopenia [27]. The SARC-F has been evaluated in three large populations including Chinese, The SARC-F has been validated in different ethnic populations and countries including Chinese, and has been proven valid and consistent for identifying those at risk of sarcopenia in these populations [13], with high specificity but relatively low sensitivity [28][29][30][31].…”
Section: Assessment Of Sarcopeniamentioning
confidence: 99%